(3GdCLhHI GdeMbbI Yf GdCSFdI GdeJaQbIs - (3GdYLdhfj , ESeGYjd Hf eMeO Hf YHO GdgGOj GdLQGMj GdOeTbj, CHh GdaOGA,J (B1162 (3g` s ((3SdjeGf Hf YHO GdgGOi s)
(3ChdgG (B:s
(3hHYO ajbhd GdabjQ Edi ehdGg GdaJGM GSeGYjd GdYLdhfi bO hbY GdSDGd Yf Md eSFdI eJfhYGJ s
(3BNQgG (B:s
(3GfJgi eG ai JdHjS EHdjS dGHf GdLhRi hGfJgi GdcJGH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B325 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B292s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B28s
Keywords: (3Gdabg GdTGaYjs